Distance Detection in the Sport of Petanque Using the VL53L0X Time-of-flight - Rizki Rizaldy, Moch. Fahmy; Anifah, Lilik (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2023)
Technology as a means to facilitate human activities is currently being applied in various fields of activity due to its rapid development. The implementation of technology has also penetrated the field of sports as a physical activity and as a solution for human physical health. Sports progress is based on the optimal state of human resources, facilities and management. With technology in the world of sports, more advanced sports are also in harmony with existing technological developments. In other sports, technology has been utilized to support and optimize the course of the sport, for example, in football with VAR and badminton with hawk-eye. Therefore, the sport of petanque, which was first popularized in Indonesia at the Sea Games in Palembang, has the potential to develop various improvements through the use of technology. The urgency faced is at the stage of measuring the distance of the ball to decide on awarding points to the team that is entitled to a Petanque match. The measuring devices and methods used are still conventional and have the potential to produce inaccurate distance values and decisions. The accuracy of the distance measurement results obtained using conventional tools and methods is questionable and raises doubts due to various factors. With the existence of distance measurement technology, it will help the referee's performance as a Petanque match court in making point decisions. The use of the VL53L0X time-of-flight (ToF) sensor has great potential because it has the advantage of good accuracy and is not affected by noise that affects the measurement results. By using the Arduino Uno R3 as a regulatory and process microcontroller and a KY-008 laser to direct and indicate the ToF sensor right at the target object. From the tests carried out, it was found that the maximum accuracy value of the prototype reached 98.45% with a standard deviation of 3.01.